Robotics: Three‐Dimensional Programmable Assembly by Untethered Magnetic Robotic Micro‐Grippers (Adv. Funct. Mater. 28/2014). (July 2014) - Diller, Eric; Sitti, Metin
<x xml:space="preserve">Abstract</x> Remotely actuated microdevices powered by magnetic fields have gained attention where a physical presence is required inside remote or enclosed microscale environments. On page 4397, E. Diller and M. Sitti demonstrate a millimeter‐scale robotic gripper capable of locomotion for precise transport, orientation, and programmable 3D assembly of microparts. The cover image illustrates a team of mobile microgrippers building a series of 3D linkage assemblies from a variety of materials in a remote fluidic channel. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>